Analysis of Physics Learning on Circular Motion Material Based on Microcontroller: A Systematic Literature Review Using PRISMA - Fauza, Naila; Septia, Audy; Yennita, Yennita (FKIP - Universitas Riau, 2025)
A microcontroller is an electronic device that can digitalize experimental tools, making them more practical and easier to use. The method used in this research is a Systematic Literature Review using PRISMA. The purpose of this study is to identify learning models, learning media, and the utilization of microcontrollers in teaching circular motion physics in schools. The collected data consists of national journal articles from accredited and indexed electronic databases, which are then extracted for content analysis. The data is subsequently analyzed and interpreted in tabular form. The findings of this study explain the learning models, learning media, and the application of microcontrollers in physics education.